Study of parenting styles, family functioning and its relation to coping strategies in children of specific learning disorder - Rupesh, Enagandula; Singh, Shipra; Subramanyam, Alka A.; Kamath, Ravindra M. (International Journal of Contemporary Pediatrics, 2020)
Background: Families of children with disabilities otherwise experience higher stress; and relation between parenting styles and coping of children is well known. Parental factors and family functioning may play a role in shaping the child, especially having issues like SLD. The objective is to study was coping strategies of children with SLD, parenting styles of their parents, their family functioning and relation of these with each other. Methods: It is a cross-sectional study undertaken after Institutional Ethics Committee approval, parent’s consent and child’s assent. Participants were 100 consecutive children, diagnosed with SLD, 9-13 years of age. Tools used were: Semi-structured proforma, Parenting Practices Questionnaire, Family Assessment Device and Children’s Coping Strategies Checklist Revision 1. Results: Authoritarian parenting style was significantly was associated with less use of ‘active’ and ‘support seeking’; and increased use of ‘distraction’ and ‘avoidance’ strategies. High scores on Authoritative style was associated with ‘active’ and ‘support seeking’ strategies. Avoidance coping strategy was associated with poor (high scores) and active coping strategies with higher (low scores) on problem solving, communication, and general family functioning. Conclusions: Parenting practices and family functioning can be pivotal in determining child’s attitude and coping. Assessment of this can be routinely included in child evaluation.